(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Healthcare is a rapidly expanding industry that includes not only medical treatments but also professional care and high-quality patient services. Fifty-eight per cent of hospitals in the nation are in the private healthcare sector. To assist various services in a hospital, there are ancillary services that add an extra benefit to the hospital for the services provided. Patients in private hospitals are the focus of this study, where the percentage measure is used in this study to assess patients’ awareness of ancillary services in private hospitals that are NABH entry-level accredited.